2018
DOI: 10.7554/elife.35710
|View full text |Cite
|
Sign up to set email alerts
|

Radical and lunatic fringes modulate notch ligands to support mammalian intestinal homeostasis

Abstract: Notch signalling maintains stem cell regeneration at the mouse intestinal crypt base and balances the absorptive and secretory lineages in the upper crypt and villus. Here we report the role of Fringe family of glycosyltransferases in modulating Notch activity in the two compartments. At the crypt base, RFNG is enriched in the Paneth cells and increases cell surface expression of DLL1 and DLL4. This promotes Notch activity in the neighbouring Lgr5+ stem cells assisting their self-renewal. Expressed by various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
(82 reference statements)
1
16
0
Order By: Relevance
“…Lfng is expressed in NEBs rather than in the NEB-associated CCs, which activates Notch signaling (Xu et al, 2010b; Xu et al, 2010a). This is reminiscent of the developing intestinal epithelium where Fringe is expressed in the ligand-presenting cells to promote Notch activity in the neighboring cells (Kadur Lakshminarasimha Murthy et al, 2018). There is currently no evidence that these proteins influence epithelial Notch signaling in the developing lung epithelium (van Tuyl et al, 2005; Xu et al, 2010b; Xu et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Lfng is expressed in NEBs rather than in the NEB-associated CCs, which activates Notch signaling (Xu et al, 2010b; Xu et al, 2010a). This is reminiscent of the developing intestinal epithelium where Fringe is expressed in the ligand-presenting cells to promote Notch activity in the neighboring cells (Kadur Lakshminarasimha Murthy et al, 2018). There is currently no evidence that these proteins influence epithelial Notch signaling in the developing lung epithelium (van Tuyl et al, 2005; Xu et al, 2010b; Xu et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…DLL4 is a Notch ligand that is essential for the homeostasis of stem and progenitor cells and the simultaneous inactivation of Dll1 and Dll4, resulting in the complete conversion of proliferating progenitors into postmitotic goblet cells, concomitant with loss of stem cells (SCs) (Olfm4(+), Lgr5(+) and Ascl2(+)) [ 21 ]. Another study showed that Dll1 and Dll4 could be regulated by Fringe proteins, such as Lfng and Rfng; the latter is enriched in Paneth cells, and the former is mainly expressed in the villus; they promote cell surface expression of DLL1 and DLL4, further contributing to Lgr5+ ISCs self-renewal [ 25 ]. The influence of PCs on intestinal stem cells is similar to that of in vitro organoids.…”
Section: Paneth Cells Mediate Intestinal Stem Cell Renewal and Regenementioning
confidence: 99%
“…DLL1 has four EGF repeats that receive O-fucose but DLL1 expressed in Pofut1 -null presomitic mesoderm or mouse embryo fibroblasts was localized to the cell surface and stimulated Notch signalling [87]. By contrast, experiments with intestinal cells showed that Paneth cells have slightly reduced cell surface expression of DLL1 and DLL4 when RFNG is absent, and cells from cultured intestinal organoids have reduced DLL1 on the cell surface after knockdown of Lfng [89]. Lfng knockout mice have reduced DLL1 and DLL4 on the surface of goblet cells, whose numbers are increased due to a reduction in Notch signalling in the absence of Lfng [89].…”
Section: O-fucose Glycansmentioning
confidence: 99%
“…By contrast, experiments with intestinal cells showed that Paneth cells have slightly reduced cell surface expression of DLL1 and DLL4 when RFNG is absent, and cells from cultured intestinal organoids have reduced DLL1 on the cell surface after knockdown of Lfng [89]. Lfng knockout mice have reduced DLL1 and DLL4 on the surface of goblet cells, whose numbers are increased due to a reduction in Notch signalling in the absence of Lfng [89]. Thus, depending on cellular context, cell surface expression of Notch ligands may be promoted by Fringe modification.…”
Section: O-fucose Glycansmentioning
confidence: 99%
See 1 more Smart Citation